Count down : how our modern world is threatening sperm counts, altering male and female reproductive development, and imperiling the future of the human race - Swan, Shanna H.; Colino, Stacey (Scribner, 2021)
"In 2017, author Shanna Swan and her team of researchers completed a major study. They found that over the past four decades, sperm levels among men in Western countries have dropped by more than 50 percent. They came to this conclusion after examining 185 studies involving close to 45,000 healthy men. The result sent shockwaves around the globe-but the story didn't end there. It turns out our sexual development is changing in broader ways, for both men and women and even other species, and that the modern world is on pace to become an infertile one. How and why could this happen? What is hijacking our fertility and our health? Count Down unpacks these questions, revealing what Swan and other researchers have learned about how both lifestyle and chemical exposures are affecting our fertility, sexual development-potentially including the increase in gender fluidity-and general health as a species. Engagingly explaining the science and repercussions of these worldwide threats and providing simple and practical guidelines for effectively avoiding chemical goods (from water bottles to shaving cream) both as individuals and societies, Count Down is at once an urgent wake-up call, an illuminating read, and a vital tool for the protection of our future"--